A framework for minimum maneuverability requirements for low earth orbit conjunction assessment, using historical conjunction data messages. Issue 3 (September 2022) - Moomey, Daniel
Abstract: Advancements in maneuver technologies such as drag enhancement devices and electric propulsion, coupled with an increasingly dynamic and congested space environment necessitate a paradigm shift to mission design and operations to mitigate the hazards and risks posed by orbital debris collisions. As the state of the orbital debris environment continues to evolve, the United States Government (USG) has increased its policy making efforts to improve space safety and environmental sustainability. Examples include revising commercial licensed launch practices through the Federal Aviation Administration (FAA), working to develop Space Traffic Management (STM) best practices through the Department of Commerce (DoC), updating the USG's Orbital Debris Mitigation Standard Practices (USG ODMSP) through the National Aeronautics and Space Administration (NASA), establishing commercial orbital debris rules through the Federal Communications Commission (FCC), and updates to Department of the Air Force and Department of Defense (DoD) space safety rules. Efforts such as these require support with adequate technical background information to inform policy decision makers. This paper discusses analyses using historical Conjunction Data Messages (CDMs) generated by the 18th Space Defense Squadron (18 SPDS). Information within these messages is analyzed to inform policy development efforts regarding proposed minimum maneuverability requirements. The analysis herein proposes minimum acceleration thresholds for space vehicle maneuverability and general minimum standards for Conjunction Assessment (CA) programs. The proposed thresholds are based on separation of orbit estimate covariances provided in CDMs, at the time of closest approach for each conjunction analyzed. Lastly, this paper proposes a regulatory framework to accompany prescriptive maneuverability thresholds, intended to help mitigate the hazards and risks to operations and the environment, posed by conjunction events involving operational space vehicles, as well as increased safety risks expected from satellite operators needing to implement maneuver capabilities for the first time.